2003
DOI: 10.1002/jmv.10454
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus DNA in corneal transplants: Prospective study of 38 recipients

Abstract: Herpes simplex virus (HSV) infection of the eye can induce epithelial and stromal keratitis and may also lead to postoperative endothelial failure in keratoplasty. Clinical symptoms and/or virus culture of corneal scrapings most frequently provide the basis for diagnosis of ocular HSV infection, and although HSV DNA has been shown to be present in the cornea, its role in success or failure of corneal grafts remains unclear. In this study, a PCR assay was used to detect HSV DNA in corneal buttons of 38 corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
(28 reference statements)
2
31
0
1
Order By: Relevance
“…As well, HSV could potentially leave the cornea associated with trafficking immune cells and then return at a later time with these cells. Nevertheless, there are numerous observations of HSV either persistent or latent in human corneas (10)(11)(12)(13)(14)(15)(16). Our observations that anterograde spread from ganglia to cornea is not required for disease predict that HSV that remains in the cornea can cause HSK.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…As well, HSV could potentially leave the cornea associated with trafficking immune cells and then return at a later time with these cells. Nevertheless, there are numerous observations of HSV either persistent or latent in human corneas (10)(11)(12)(13)(14)(15)(16). Our observations that anterograde spread from ganglia to cornea is not required for disease predict that HSV that remains in the cornea can cause HSK.…”
Section: Resultsmentioning
confidence: 78%
“…Viral DNA and infectivity are frequently found in human tears and in corneas removed for transplantation (9,(11)(12)(13). Moreover, infectious virus can cause damage to corneas during storage or be transmitted to recipients (9,14,15), and this virus is unlikely to be derived from reactivating neurons, given the time frame of the surgery. Similarly, in rabbits and mice, persistent HSV DNA has also been detected in the corneas long after acute infections have subsided (16,17).…”
mentioning
confidence: 99%
“…However, studies from mice indicate that lytic transcripts and proteins are expressed at very low levels in latently infected ganglia (26)(27)(28). There is also human observational data based on tissue sampling, which demonstrated expression of HSV-1 genes during latency (29)(30)(31)(32). Previously we have shown that this low level of HSV-1 gene expression in the presence of LAT is associated with T cell exhaustion in TG of latently infected mice (28).…”
mentioning
confidence: 98%
“…However, studies in mice indicate that lytic transcripts and proteins may be expressed at very low levels in latently infected ganglia (15,40). There is also human observational data based on tissue sampling which demonstrated expression of HSV-1 genes during latency (11,28,61,62). Whether this low-level HSV-1 gene expression represents reactivation events or indicates continued low-level viral gene expression during latency remains unclear.…”
mentioning
confidence: 99%